Age-related macular degeneration (AMD) – epidemiology of the 21st century - Mackiewicz, Jerzy; Dolar-Szczasny, Joanna; Bieliński, Paweł (Polish Journal of Public Health, 2010)
Introduction. Age-related macular degeneration (AMD) is the leading cause of legal blindness in the industrialized world over the age of 50. Despite intensive efforts to understand AMD pathogenesis, the course and treatment options for this disease remain basically unknown. Aim. The aim of the study is the epidemiological evaluation of age-related macular degeneration (AMD) occurrence in south-east Poland with particular consideration of retinal pigment epithelium layer and photoreceptors integrity in various AMD stages according to the obtained fundus autofluorescence images of the eye. Material and methods. Two hundred patients (322 eyes) with different forms of AMD sent to the Ophthalmology Clinic in Lublin were included in the study. Mean age was 70 years (49-91 years). Apart from the complete ophthalmological examination the patients were examined every 6 months by using a confocal scanning ophthalmoscope (Heidelberg Retina Angiograph 2- HRA2). The follow-up period was from one to 40 months (mean – 18 months). Results. In 116 eyes with early AMD punctuate changes in autofluorescence images and in 22 eyes (16%) no distinct changes were observed. In 52 eyes (62%) with wet AMD, normal or near normal autofluorescence signal was present and the rest – 34 eyes (38%) had changes in the autofluorescence signal corresponding with the CNV area. All the eyes with disciform scar were characterized by uneven autofluorescence signal decrease in the scar area with an increased signal in the surroundig area. Eyes with geographic atrophy (GA) lacked the autofluorescence signal corresponding to RPE atrophy and in 40 cases (95%) increase autofluorescence signal junctional to GA was noted. Conclusion. The fact that AMD is more often diagnosed among city inhabitants comparing to inhabitants of rural regions may be due to better accessibility of ophthalmologists in urban than in agricultural areas. The presence of respective AMD forms in our study does not differ from those in the literature. Fundus autofluorescence images of the AMD eyes vary greatly and may be helpful in monitoring the course of AMD.